Hubungan Kemampuan Komunikasi Terapeutik Perawat Dengan Kepuasan Pasien Di Ruang Rawat Inap Rumah Sakit - Agil, Hilda Meriyandah; Mulyani, Puji Sri; Deniati, Kiki (Rumah Sakit Ibnu Sina, Makassar, 2022)
Nursing service is a form of professional service that is an integral part of health services based on nursing knowledge and tips aimed at individuals, families, groups, or communities, both healthy and sick. One indicator of the success of hospital services is an evaluation of customers’ satisfaction. In health services, patient satisfaction also determines the quality of health services provided. One of the factors that influence patient satisfaction with nursing services is the therapeutic communication factor. In this case, it is expected that nurses are skilled in receiving and responding to patient complaints with therapeutic communication techniques. This study aims to determine the relationship between nurses' therapeutic communication skills and client satisfaction in the inpatient ward of X Hospital in Bekasi. This research is quantitative research with an analytical descriptive method with a cross-sectional approach. The research sample was from the inpatient ward patients' internal medicine room. Based on the purposive sampling technique, the number of samples was determined by 42 patients. The results of the study concluded that there was a relation between nurses' therapeutic communication skills and client satisfaction in the X Hospital inpatient room. Hospital X is expected to provide additional training for nurses in conducting therapeutic communication in order to increase client satisfaction.